Lewis Acid Mediated [3+2] and [3+3] Annulations of an Azomethine Imine with Donor–Acceptor Cyclopropanes - Mandadapu, Raghuramaiah; Dehade, Amol Satish; Shete, Shrikant Abhiman; Montgomery, Mark; Sikervar, Vikas; Sonawane, Ravindra (Synthesis, 2021)
Two different Lewis acids were used for developing [3+2] and [3+3] regioselective cycloaddition reactions of an azomethine imine with activated cyclopropanes. Scandium(III) triflate catalyzes a [3+2] cycloaddition reaction of the azomethine imine with cyclopropanes to form tetrahydropyrazolone derivatives and tricyclic tetrahydrofuran derivatives in moderate yields. Complementary to this, a novel [3+3] cycloaddition reaction of the azomethine imine with activated cyclopropanes was developed by using EtAlCl2 as a Lewis acid to form hexahydropyridazinone derivatives in high regioselectivity.
Keywords: pyrazolidines; [3+2] cycloaddition; [3+3] cycloaddition; azomethine imines; donor–acceptor cyclopropanes